Perbedaan Kinerja Keuangan dan Abnormal Return Sebelum dan Sesudah Akuisisi di BEI - Lesmana, Fuji Jaya; Gunardi, Ardi (Jurnal Trikonomika, 2012)
This research aimed at knowing the companiesâ financial performance before and after acquisition (comparison study) of both the acquirer and acquired companies. The result showed that the financial performance of the acquirer companies was not significantly improved. But after performing acquisition, their financial performance showed an improvement - better than prior to the acquisition. The financial performance of acquired companies was not significantly improved either. But, after being acquired their financial performance showed an improvement - better than before being acquired.